A chromosome‐scale genome assembly reveals a highly dynamic effector repertoire of wheat powdery mildew. Issue 4 (14th November 2018) - Müller, Marion C.; Praz, Coraline R.; Sotiropoulos, Alexandros G.; Menardo, Fabrizio; Kunz, Lukas; Schudel, Seraina; Oberhänsli, Simone; Poretti, Manuel; Wehrli, Andreas; Bourras, Salim; Keller, Beat; Wicker, Thomas
Summary: Blumeria graminis f. sp. tritici ( B.g. tritici ) is the causal agent of the wheat powdery mildew disease. The highly fragmented B.g. tritici genome available so far has prevented a systematic analysis of effector genes that are known to be involved in host adaptation. To study the diversity and evolution of effector genes we produced a chromosome‐scale assembly of the B.g. tritici genome. The genome assembly and annotation was achieved by combining long‐read sequencing with high‐density genetic mapping, bacterial artificial chromosome fingerprinting and transcriptomics. We found that the 166.6 Mb B.g. tritici genome encodes 844 candidate effector genes, over 40% more than previously reported. Candidate effector genes have characteristic local genomic organization such as gene clustering and enrichment for recombination‐active regions and certain transposable element families. A large group of 412 candidate effector genes shows high plasticity in terms of copy number variation in a global set of 36 isolates and of transcription levels. Our data suggest that copy number variation and transcriptional flexibility are the main drivers for adaptation in B.g. tritici . The high repeat content may play a role in providing a genomic environment that allows rapid evolution of effector genes with selection as the driving force.